Development of Interactive Learning Media on Simple Flat Buildings Material "BADANA" for Students Grade III Elementary School - Novia Sari; Yeni Yuniarti (Jurnal Inovasi Matematika, 2023)
The purpose of this research is to produce a product from the design of interactive learning media articulating the "BADANA" storyline. This study describes the feasibility of media resulting from the validation of material experts, media experts, and linguists. Furthermore, the response of teachers and students as users of the use of interactive learning media "BADANA". The model used is the ADDIE model which includes five stages including analysis, design, development, implementation, and evaluation. Furthermore, for the subject of this study, namely class III students one of SD Negeri in Sindanglaya. The feasibility of this interactive learning media resulted in that the percentage of assessments from material experts was 100% in the "Very Feasible" category, from media experts it was 96.1% in the "Very Feasible" category and from linguists it was 91.6% in the "Very Feasible" category. While the percentage of responses from teachers was 93.7% in the "Very Feasible" category, indicating that this interactive learning media can be used by students. After students used interactive learning media in field trials, student responses were in the "Very Feasible" category with a percentage of 95.9%. Therefore the interactive media articulate storyline "BADANA" can be used as an alternative in the learning process which can overcome the lack of interest of students when learning mathematics, especially on flat material and its properties.